Urinary Human Kidney Injury Molecule1- (hKIM1-) is not Increased in Patients with Renal Cell Carcinoma - Bialek, Lukasz; Poletajew, Slawomir; Niemczyk, Michal; Czerwinska, Katarzyna; Nowak, Mateusz; Sadowska, Anna; Borkowski, Tomasz; Radziszewski, Piotr; Dobruch, Jakub; Kryst, Piotr (Urology Journal, 2020)
Purpose: Human Kidney Injury Molecule-1 (hKIM-1) was proposed as urinary biomarker of renal cell carcinoma (RCC). The aim of the study was to validate urinary hKIM-1 as a biomarker of RCC. Material and methods: Forty-six participants were enrolled into the study, including 30 patients with clear-cell or papillary RCC and 16 matched patients in the comparison group. Preoperative urinary hKIM-1 levels were measured using commercially available ELISA kit and normalized to urinary creatinine levels. Results: The concentrations of urinary hKIM-1 normalized to urinary creatinine in patients with RCC and comparison group did not differ significantly (1.35 vs. 1.32 ng/mg creatinine, p=.25). There was also no difference in urinary hKIM-1 concentration regarding stage or grade of renal cancer. Additional analysis of patients without chronic kidney disease (defined as eGFR ≥60mL/min/1.73m²) also did not reveal significant difference in urinary hKIM-1 concentrations between the groups (1.54 vs. 1.37; p=.47). Conclusion: Results of our study do not confirm recent suggestions that urinary hKIM-1 may be a biomarker of RCC.